2020
DOI: 10.1007/s11085-020-10001-y
|View full text |Cite
|
Sign up to set email alerts
|

Surface Roughness Evolution to Identify Incubation Time for Hot Corrosion of Nickel-Base Superalloys: CMSX-4, CM247LC DS and IN6203DS at 550 °C

Abstract: In the absence of protective scales, nickel-base superalloys have an extremely limited hot corrosion incubation period before increased rates of attack are experienced. This paper reports on the nickel-base superalloys: CMSX-4, CM247LC DS and IN6203DS subjected to 550 °C hot corrosion exposures of durations ranging from 0 to 800 h, during which none of the superalloys developed a fully protective scale. The aim of the research was to identify the incubation period of each superalloy and this was achieved by me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Similar hot corrosion exposures to those performed by Kistler et al [14] have also been performed on CMSX-4, CM247LC DS and IN6203DS using a 4/1 molar ratio of Na 2 SO 4 :K 2 SO 4 deposits, with a surface loading of 0.5 mg cm −2 applied every 100 h, in a gaseous environment of 300 ppm SO 2 in air at 550 °C [15]. Those exposures indicated that a continuous layer of protective scale had failed to establish itself at the relatively low temperature.…”
Section: Introductionmentioning
confidence: 56%
See 3 more Smart Citations
“…Similar hot corrosion exposures to those performed by Kistler et al [14] have also been performed on CMSX-4, CM247LC DS and IN6203DS using a 4/1 molar ratio of Na 2 SO 4 :K 2 SO 4 deposits, with a surface loading of 0.5 mg cm −2 applied every 100 h, in a gaseous environment of 300 ppm SO 2 in air at 550 °C [15]. Those exposures indicated that a continuous layer of protective scale had failed to establish itself at the relatively low temperature.…”
Section: Introductionmentioning
confidence: 56%
“…Cylindrical specimens were used to evaluate the evolution of surface roughness during exposure to the hot corrosion conditions [15]. The data obtained were gathered during a metrology exercise on the polished cross-sections and enabled equations to be derived which provided an estimation of the maximum penetration rate of hot corrosion during the propagation stage of attack.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations